Short-Term Results of Sclerotherapy with 3% Polidocanol Foam for Symptomatic Second- and Third-Degree Hemorrhoidal Disease. Issue 10 (17th September 2021) - Lobascio, Pierluigi; Laforgia, Rita; Novelli, Eugenio; Perrone, Fabrizio; Di Salvo, Maria; Pezzolla, Angela; Trompetto, Mario; Gallo, Gaetano
Abstract: Background: Hemorrhoidal disease (HD) is defined as the symptomatic enlargement and/or distal displacement of anal cushions and is one of the most common proctological diseases. Sclerotherapy (ST) with 3% polidocanol foam induces an inflammatory reaction with sclerosis of the submucosal tissue and consequent suspension of the hemorrhoidal tissue. The aim of this study was to evaluate the short-term effectiveness and safety of ST with 3% polidocanol foam for the treatment of symptomatic second- and third-degree HD. Methods: A total of 66 patients with symptomatic second- and third-degree HD underwent a single ST session between March 2017 and July 2018. A visual analog scale score was used to assess post-operative pain and patient satisfaction. The symptoms severity and anal continence were investigated through the Hemorrhoid Severity Score (HSS) and Vaizey score, respectively, at baseline, at 4 weeks and after 1 year. Results: Fifty-seven out of 66 patients were male (86.3%), and the mean age was 52 (29–75; SD ± 12) years. The mean operative time was 4.5 (2–6; SD ± 1.23) minutes. No intraoperative complications and no drug-related side effects occurred. The overall success rate was 78.8% (52/66 patients) after a single ST session and 86% after two ST sessions (57/66 patients). The mean treatment effect, obtained comparing preoperative and 12 months symptom scores in each patient, showed a median change of 8 ( p < 0.001). All patients resumed their normal daily activities the day after the procedures. Conclusions: ST with 3% polidocanol foam is a safe, cost-effective and repeatable conservative treatment.